Forecast optimal fluoride concentration data in drinking water according to the ambient temperature in Golestan, Iran. Issue 3 (26th March 2019) - Zazouli, Mohammad Ali; Kalankesh, Laleh R.; Hasanpour, Maryam
Abstract: Controlling fluoride concentrations in drinking water at optimal levels could be effective in preventing certain negative health effects in humans. This study investigated optimal fluoride concentrations in potable water in Golestan province, according the ambient temperatures in the province. The study used data on fluoride concentrations in drinking water supplied by the Water and Wastewater Company of Golestan Province. The annual mean maximum temperatures were extracted from a website that recorded daily ambient temperature. The optimal value of fluoride in drinking water for each county of Golestan province was calculated by the Galgan and Vermillion formula. The results show that all of the counties should contain fluoride concentrations ranging from 0.73 to 0.766 milligrams per liter (mg/L) according to the calculation formula, while fluoride concentrations were instead reported to range between 0.23 and 0.53 mg/L by the Water and Wastewater company. In addition, according to World Health Organization (WHO) recommendations, the concentrations of fluoride in potable in all of the cities in Golestan province fall below the WHO standard. In conclusion, we suggest that the fluoride concentrations in Golestan province's drinking water should be taken into account by the appropriate authorities and that optimal fluoride concentrations in drinking water according to ambient temperatures be set to avoiding negative health impacts.